The effectiveness of self-management support interventions for men with long-term conditions: a systematic review and meta-analysis. Issue 3 (20th March 2015) - Galdas, Paul; Fell, Jennifer; Bower, Peter; Kidd, Lisa; Blickem, Christian; McPherson, Kerri; Hunt, Kate; Gilbody, Simon; Richardson, Gerry
Abstract : Objectives: To assess the effectiveness of self-management support interventions in men with long-term conditions. Methods: A quantitative systematic review with meta-analysis. Data sources: The Cochrane Database of Systematic Reviews was searched to identify published reviews of self-management support interventions. Relevant reviews were screened to identify randomised controlled trials (RCTs) of self-management support interventions conducted in men alone, or which analysed the effects of interventions by sex. Review methods: Data on relevant outcomes, patient populations, intervention type and study quality were extracted. Quality appraisal was conducted using the Cochrane Risk of Bias Tool. Meta-analysis was conducted to compare the effects of interventions in men, women, and mixed-sex sub-groups. Results: 40 RCTs of self-management support interventions in men, and 20 eligible RCTs where an analysis by sex was reported, were included in the review. Meta-analysis suggested that physical activity, education, and peer support-based interventions have a positive impact on quality of life in men. However, there is currently insufficient evidence to make strong statements about whether self-management support interventions show larger, similar or smaller effects in men compared with women and mixed-sex groups. Conclusions: Clinicians may wish to consider whether certain types of self-management support (eg, physical activity, education, peer support) are particularly effective in men, although more research is needed to fully determine and explore this.